Luteolin potentiates the effects of aminoglycoside and β-lactam antibiotics against methicillin-resistant Staphylococcus aureus in vitro - JOUNG, DAE-KI (Exp Ther Med, 2016)
Methicillin-resistant Staphylococcus aureus (MRSA) infection has become a serious clinical problem worldwide, and alternative natural or combination drug therapies are required for its treatment. The aim of the present study was to examined the antimicrobial activity of luteolin (LUT) against MRSA. Luteolin is a polyphenolic flavonoid compound with a wide spectrum of biological activities. The antimicrobial activities of LUT and the antibiotics ampicillin (AM), oxacillin (OX) and gentamicin (GT), used alone or in combination, were evaluated against five clinical MRSA isolates and two reference strains using a minimum inhibitory concentration (MIC) assay, MTT colorimetric assay, checkerboard dilution test and time-kill assay. The MIC of LUT against all strains was found to be 62.5 µg/ml. The combinations of LUT and antibiotics exhibited a synergistic effect against MRSA in the majority of cases, as determined by the checkerboard method. Time-kill curves revealed that a combination of LUT with AM, OX or GT significantly reduced bacterial counts, which dropped below the lowest detectable limit after 24 h. These results indicate that LUT potentiates the effects of β-lactam and aminoglycoside antibiotics against MRSA.